KEPENTINGAN PEMERINTAH KOTA PADANG DALAM MENJALIN KERJA SAMA SISTER CITY DENGAN PROVINSI BA RIA-VUNG TAU (VIETNAM) - Fadillah, M. Fariz Akbar; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research analyzed the interests of the Padang City Government in establishing a Sister City Cooperation with Ba Ria-Vung Tau Province (Vietnam). The Padang City Government had carried out cooperation since the signing of the Memorandum of Understanding (MoU) in 2016. This cooperation involved sub- state actors in international relations activities, which was included in the paradiplomacy phenomenon as an effort to fulfill regional interests in advancing regional capabilities or potentials in accordance with the mandate of regional autonomy policies. The Padang City Government and Ba Ria-Vung Tau Province had their respective regional government interests in implementing cooperation to achieve their common interests. This research employed a qualitative method, namely through interviews and library studies, as well as secondary data materials. The research utilized the perspective of liberalism and paradiplomacy theory, where paradiplomacy refers to the ability of sub-state actors to become actors in international relations. The findings of this research indicated that the interests of the Padang City Government in establishing a Sister City Cooperation with Ba Ria-Vung Tau Province were to maximize the capabilities of its region, boost the economy that had declined in 2013, and resolve various issues in the agreed-upon cooperation fields. By utilizing this research as a policymaking consideration, the Padang City Government and other local governments seeking to engage in international cooperation as sub-state actors could take appropriate steps. Keywords: Interests, Sister city, Paradiplomacy, Padang City, Ba Ria-Vung Tau Province